Unmasking leading to a healthcare worker Mycobacterium tuberculosis transmission. Issue 4 (December 2018) - Holden, K.L.; Bradley, C.W.; Curran, E.T.; Pollard, C.; Smith, G.; Holden, E.; Glynn, P.; Garvey, M.I.
Summary: Background: Mycobacterium tuberculosis is a major health burden worldwide. The disease may present as an individual case, community outbreak, or more rarely as a nosocomial outbreak. Even in countries with a low prevalence such as the UK, tuberculosis (TB) presents a risk to healthcare workers (HCWs). Aim: To report an outbreak which manifested 12 months after a patient with pulmonary tuberculosis was admitted to Queen Elizabeth Hospital Birmingham. Methods: We present the epidemiological and outbreak investigations; the role of whole genome sequencing (WGS) in identifying the outbreak and control measures to prevent further outbreaks. Findings: Subsequent to a diagnosis of open TB in a patient, transmission was confirmed in one HCW who had active TB; HCWs with latent TB infection (LTBI) were also identified among seven HCW contacts of the index patient. Of note, all the LBTI patients had other risk factors for TB. Routine use of WGS identified the outbreak link between the index patient and the HCW with active TB disease, and informed our investigations. Conclusion: Exposure most likely occurred during an aerosol-generating procedure (AGP) which was done in accordance with national guidance at that time without using respiratory protection. Enhanced control measures were implemented following the outbreak.